Trends of multimorbidity in 15 European countries: a population-based study in community-dwelling adults aged 50 and over - Souza, Dyego L B; Oliveras-Fabregas, Albert; Minobes-Molina, Eduard; de Camargo Cancela, Marianna; Galbany-Estragués, Paola; Jerez-Roig, Javier (BMC public health, 2021)
BACKGROUND: The objective of this work was to analyse the prevalence trends of multimorbidity among European community-dwelling adults. METHODS: A temporal series study based on waves 1, 2, 4, 5, 6 and 7 of the Survey of Health, Ageing and Retirement in Europe (SHARE) was conducted, and community-dwelling participants aged 50+ (n = 274,614) from 15 European countries were selected for the period 2004-2017. Prevalence, adjusted by age, Average Annual Percentage Change (APC) and 95% confidence interval (95% CI) were all calculated. Trend analyses were realised by period, age groups and groups of diseases. RESULTS: The results showed a large variability in the prevalence of multimorbidity in adults aged 50 and over among European countries. Increase in the prevalence of multimorbidity in the countries of central Europe (Austria, Belgium, Czech Republic, France, Germany and Switzerland) and Spain in both sexes, and in the Netherlands among men. Stability was observed in northern and eastern European countries. Musculoskeletal and neurodegenerative groups showed more significant changes in the trend analyses. CONCLUSIONS: This information can be useful for policy makers when planning health promotion and prevention policies addressing modifiable risk factors in health.
Keywords: samostatný způsob života; Netherlands; Belgie; Germany; Španělsko; Belgium; Independent Living; Německo; multimorbidita; Humans; Male; Švýcarsko; Evropa; Spain; Multimorbidity; Aged; lidé středního věku; Europe; ženské pohlaví; Czech Republic; Francie; Prevalence; Adult; mužské pohlaví; dospělí; Middle Aged; Česká republika; Nizozemsko; Rakousko; Austria; lidé; SHARE; Older adults; Non-communicable diseases; senioři; Switzerland; Female; France